The relationship between services quality and customers satisfaction at Institut Amiduddin Baki (IAB) in Kedah / Najmi Nadhirah Rodzli - Rodzli, Najmi Nadhirah (2014)
Service quality is conceptualized as the difference between customer expectation for services performance prior to the services encounter and their perception of the actual service received. Service quality is equal to the difference between the perception and expectation. Services quality also become an important antecedent to customer satisfaction, which is inextricably linked to consumer pre-purchased behavior and consumption decision making. Quality plays an important role to the company that should be understood properly. This research is focused on the services quality and customer satisfaction at Institut Aminuddin Baki (IAB) Cawangan Utara, Kedah. The objective of this study is to identify the factors of services quality that influence customer satisfaction at Institut Aminuddin Baki (IAB) Cawangan Utara, Kedah. About 103 questionnaires were distributed among the customers who comes to Institut Aminuddin Baki (IAB) Cawangan Utara. The study has shown that the Institut Aminuddin Baki (IAB) Cawangan Utara take services quality and customer satisfaction as one of important aspects in order to improve their services towords the customers. Based on the findings, it was conclude that Institut Aminuddin Baki (IAB) is a good and comfortable place to the customers. The study also shows that there was a relationship between customer satisfaction and service quality at Institut Aminuddin Baki (IAB). In the end, the study had provided several recomendation in order to increase the service quality as well to have the customers satisfaction.